Prioritisation of functional needs for ICU intelligent robots in China: a consensus study based on the national survey and nominal group technique - Hao Wang; Ying Bai; Fan Zhang; Shuya Wang; Zhen Cui; Xin Yuan; Liu Zhang; Xinbao Wu; Yufeng Yan; Miaomiao Yu; Bo Ouyang (BMJ Open)
Objective This study aims to define the prioritisation of the needs for an intelligent robot’s functions in the intensive care unit (ICU) from a clinical perspective.Design This study introduces a nominal group technique.Setting This study uses national setting.Participants This study includes a total of 851 respondents from 34 provinces in China who participated in the survey. A nominal group of 12 members was organised by the research group; there were seven experts with a background in critical care, two junior attending physicians with a background in critical care and three experienced nurses.Results A total of 50 needed intelligent robot functions in ICUs were obtained from the questionnaire data. Through three rounds of nominal group voting and discussion, a consensus was reached on 44 items, which were categorised into 29 high-priority needs, 13 medium-priority needs and two low-priority needs. The functionalities in areas such as ‘sleep and pain assessment,’ ‘monitoring of sedation, agitation, and delirium,’ and ‘robot-assisted rehabilitation and physical therapy’ were particularly favoured by the ICU medical and nursing staff.Conclusions This study has defined the functional needs and priorities for ICU intelligent robots from the perspective of ICU clinical medical and nursing staff. It has been concluded that ‘disease assessment function’ and ‘rehabilitation and physical therapy’ are most needed by clinical doctors and nurses. The results presented in this study could serve as a useful reference for future research and development of medical robots.